2017
DOI: 10.1038/srep42976
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal prophages are diverse, but not without structure or history

Abstract: Bacteriophages (phages) infect many bacterial species, but little is known about the diversity of phages among the pneumococcus, a leading global pathogen. The objectives of this study were to determine the prevalence, diversity and molecular epidemiology of prophages (phage DNA integrated within the bacterial genome) among pneumococci isolated over the past 90 years. Nearly 500 pneumococcal genomes were investigated and RNA sequencing was used to explore prophage gene expression. We revealed that every pneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
80
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(89 citation statements)
references
References 39 publications
9
80
0
Order By: Relevance
“…We had previously determined the prevalence, diversity and molecular epidemiology of full-length prophages in a global and historical pneumococcal genome dataset 26 . Many shorter prophage sequences were also identified in that study, which were simply classified as partial prophage sequences and not characterised further at the time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We had previously determined the prevalence, diversity and molecular epidemiology of full-length prophages in a global and historical pneumococcal genome dataset 26 . Many shorter prophage sequences were also identified in that study, which were simply classified as partial prophage sequences and not characterised further at the time.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that pneumococcal full-length prophages were consistently integrated in specific locations within the genome 26 . Likewise, pneumococcal satellite prophages were consistently integrated in seven precise locations (a-f) within the host genome, each of which was directly associated with the integrase gene they harboured (Figure 3d; Figure 4a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Resolution rules for ICE/phage double calls were based on inspection of the 26 instances found among TIGER/Islander, temperate phage, and ICE datasets. Phage1/ICE double calls were found to be either an unresolved ICE/phage tandem or an IGE of one type integrated within another (54), yielding a new category of IGE call (ICE+Phage). Phage2/ICE double calls were converted to the ICE call.…”
Section: Methodsmentioning
confidence: 99%
“…The exceptions were the blp clusters: their highly diverse and complicated genetic compositions among pneumococci genomes meant that a similar classification between partial and complete clusters could not be applied (ref. 12). Instead, their presence (irrespective of being partial or complete) is depicted by the green colour.…”
Section: Data Accessmentioning
confidence: 99%